1984
DOI: 10.1080/01811797.1984.10824641
|View full text |Cite
|
Sign up to set email alerts
|

Polyphylétisme des campanules annuelles

Abstract: Les campanules annuelles, extrêmement complexes (6 sous-genres), sont d'origine polyphylétique. L'auteur montre que des lignées différentes ont pris naissance, soit par dysploïdie, de type descendant, accompagnée parfois de polyploïdie, soit à partir d'espèces vivaces avec lesquelles elles présentent de réelles affinités (dans ce cas, les annuelles ont le même nombre chromosomique ou un nombre dérivé de celui des espèces vivaces). Enfin, certaines annuelles forment avec des taxons vivaces et bisannuels de gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…High levels of extinction could potentially explain the current disjunct distribution of C. fastigiata in both western and eastern Mediterranean regions. Finally, the present clade also supports a new switch from the annual to perennial condition, a rather common episode in Campanula evolution [82] the potential causes of which would deserve more investigations.…”
Section: Discussionsupporting
confidence: 61%
“…High levels of extinction could potentially explain the current disjunct distribution of C. fastigiata in both western and eastern Mediterranean regions. Finally, the present clade also supports a new switch from the annual to perennial condition, a rather common episode in Campanula evolution [82] the potential causes of which would deserve more investigations.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, plants included in subgenus Megalocalyx show tubular‐campanulate or nearly rotate corollas, the style is smaller (4–15 mm long) and always included in the corolla. Some authors (Contandriopoulos, 1972, 1976, 1984; Gadella, 1966; Damboldt, 1978) suggested that Sicyocodon with its long exserted style probably holds a very isolated position in the genus, which is attributed to a different pollination syndrome related to flies, unique in the Campanulaceae (Damboldt, 1978). Plants included in the genus Campanula , and particularly those in subgen.…”
Section: Introductionmentioning
confidence: 99%